Hubungan Antara Zakat, Infak dan Sedekah dengan Nilai-nilai Sosial Masyarakat - Suhartono; Suwandi; Tasdiq; Muhadi; Mohammad Rifa'i (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Nurul Huda, 2024)
This study aims to analyze the issues of zakat, infak, and sedekah, the social values derived from zakat, infak, and sedekah, and the relationship between zakat, infak, and sedekah with the social values of society. The research method used in this study is library research to investigate and analyze the literature related to the concepts of zakat, infak, and sedekah and their relationship with the social values of society. Data were collected from various information sources such as literature, scientific articles, books, and journals relevant to the research topic. The results of this study include: (1) Zakat is an obligation in Islam that requires Muslims to give a portion of their wealth to those who are entitled (mustahik zakat). Infak is a voluntary contribution for goodness or humanity, while sedekah is the act of giving without regard to the status of the recipient. (2) The social values of zakat, infak, and sedekah include justice, solidarity, empathy, and social welfare. (3) The relationship between zakat, infak, and sedekah with the social values of society includes: (a) wealth redistribution and social justice, (b) building solidarity and social care, (c) helping poverty alleviation and improving welfare, (d) economic empowerment and independence, and (e) strengthening religious and moral values.